ANALISIS YURIDIS PERMOHONAN JUDICIAL REVIEW PENGHAPUSAN PASAL DENGAN FRASA UMRAH MANDIRI PADA UNDANG UNDANG NO.14 TAHUN 2025 TENTANG PERUBAHAN KETIGA ATAS UNDANG UNDANG NO. 8 TAHUN 2019 TENTANG PENYELENGGARAAN IBADAH HAJI DAN UMRAH - Firman Adi Candra, (Journal of Innovation Research and Knowledge, 2026)
The implementation of the Hajj and Umrah pilgrimages is the right of Indonesian citizens who are Muslim to worship as mandated in Article 28E paragraph (1) of the 1945 Constitution of the Republic of Indonesia. The implementation of the Hajj and Umrah pilgrimages is a series of religious worship which is the responsibility of the state and its implementation is guaranteed in accordance with the mandate of Article 28I paragraph (4) and Article 29 of the 1945 Constitution of the Republic of Indonesia. The state's responsibility to fulfill the right to perform the Hajj and Umrah pilgrimages as human rights is realized by providing guidance, services and protection for Indonesian citizens who perform the Hajj and Umrah pilgrimages so that they can be carried out safely, peacefully, orderly and in accordance with sharia provisions. The Hajj and Umrah pilgrimages are spiritual activities that convey the meaning of gratitude, sacrifice, and carrying out God's commands. They are good because they teach self-control, require considerable effort, volunteerism, and sincerity in giving away wealth, among other things. In reality, the Hajj and Umrah pilgrimages are not only contained in Islamic law but are also regulated by positive legal regulations in Indonesia. The process of performing the Hajj and Umrah in Indonesia is also quite lengthy, from registration and departure from Indonesia, to pick-up, and finally, the return flight.